EVALUATION OF DECELLULARISATION PROTOCOLS FOR DEVELOPING EXTRACELLULAR MATRIX BASED PORCINE TUNICA VAGINALIS SCAFFOLDS FOR TISSUE ENGINEERING APPLICATIONS - Prabhachandran Sobhana Arathy; Dhanush Krishna Balakrishnan-Nair; Divya C; V. N. Vasudevan; I.S. Sajitha; Jessil Joseph; Safeer M. Saifudeen; K.S. Prasanna (Exploratory Animal and Medical Research, 2023)
The relevance of biomaterials to successfully restore the function of lost tissues to improve human health is increasing. There is a need to develop new biocompatible, low-cost biomaterial with better strength that can perform the intended purpose. Porcine tunica vaginalis, - a readily available abattoir bio-waste from slaughterhouses and being an expansion of the peritoneum into the scrotum, can be considered a candidate scaffold. A study was carried out to examine the in-vitro characteristics of variably decellularised porcine tunica vaginalis. The native or non-decellularised tissue was maintained as a control group (PTV). The varied protocols for decellularisation included (a) Trypsin-EDTA-Triton-X-100 treated tunica vaginalis (DTV1) (b) Sodium deoxycholate (SDC) and DNase treated porcine tunica vaginalis (DTV2) and (c) a combined protocol (DTV3) for decellularising porcine tunica vaginalis. The efficiency of decellularisation was evaluated by histological examination, DNA quantification, and 4, 6- diamidino-2-phenylindole (DAPI) nuclear staining. The biomechanical properties of the materials were examined by analyzing tensile strength, maximum load at the break, and Young’s modulus. Further, the surface and other structural characteristics were analyzed using scanning electron microscopy and special staining techniques. The concentration of DNA, nuclear staining, and surface characters was in an acceptable range after decellularization for all three scaffolds. All decellularisation protocols reduced DNA concentration significantly compared to the non-decellularised control and retained collagen and other extracellular matrices (ECM) components. However, the DTV3 scaffold revealed minimal nuclear remnants, acceptable DNA concentration as well as good surface topography. Comparison of biomechanical characters of the decellularised scaffolds with non-decellularised tissue evidenced better tensile strength and Young’s modulus for DTV3. This work highlights the influence of different decellularisation protocols on the final scaffolds which could pave the way for developing a novel scaffold that can address various clinical problems in the medical field.